Dermatofibrosarcoma Protuberans: A Rare Cause of Neck Swelling - Rahman, Md Abdur; Alam, Mahbubul; Kabir, ABM Luthful; Rarhid, Mohammod Harun Or; Prodhan, Abul Kalam (Bangladesh Journal of Otorhinolaryngology, 2020)
Dermatofibrosarcomaprotuberans (DFSP) is a low-grade soft tissue sarcoma (fibrosarcoma) originated from dermal and subdermal layer of the skin. The tumor infiltrates into the deeps in the form of villous or finger. For this reason, it is quite difficult to get clear surgical margins during tumor excision and the recurrence is a problem encountered frequently. We are reporting this rare tumour in a 40-year-old man presented with a 5-years history of slowly growing cutaneous lesion of the neck. Incisional biopsy confirmed the diagnosis of DFSP. Subsequently, the patient underwent wide local surgical resection, followed by reconstruction. Histopathology report revealed dermatofibrosarcomaprotuberans (DFSP). Although DFSP behave as non-aggressive malignancy, surgery with complete removal of the affected area is the treatment of choice. Moreover, adjuvant radiotherapy and follow-up of the patient is essential in order to prevent recurrence. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 110-113